(untitled) (MMIT Proceedings, 2024)
In this article, the author discusses the current trends in inclusive education in Uzbekistan, focusing on school education as an example. The author highlights the dynamics of inclusive education in the schools of the country and emphasizes the socio-cultural aspects of this process. Additionally, the author provides insights into global trends in inclusive education.